Negative Revenue and Economic Degrowth - Cante Maldonado, Freddy Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The objective of the author in this text is to defend the following working hypothesis: the increasing use, alteration and extraction of natural resources, and currency speculation, generate different revenues but involve the subtraction of non-renewable resources and, in addition, generate a magnified and accelerated degradation of the environment, and produce social costs, so that revenues should be negative. The methodology used is to put forward a critical interpretation of the conventional concept of revenue and, based on heterodox and unconventional economic theories and someempirical evidence from secondary sources, to find a theoretical result, which consists of the negative revenue proposal. Specifically, the revenues from fossil fuels, gold, and money are discussed. Finally, some guidelines are shown on how negative revenue would work. The main implication of this study is that negative revenue leads to an economic policy oriented towards degrowth.